A propaganda publicitária e sua significação no simbólico coletivo: análise discursiva de propagandas publicitárias do governo Dilma - Silva, Evilasio dos Santos (2013)
Advertising is currently seen as a system of indoctrination and framework of a population to a particular system of ideas and values. She may be able to detain individuals, producing meanings which are of actually framing the population within a given system of ideas and values. Therefore, the text of the advertisements, or about them, can not be analyzed as given without recourse to linguistic memory, but as fact. It needs to be understood as having more than the function to inform, disseminate, remember and remind the consumer that the product exists and undoubtedly will bring benefits to him who acquire. It is necessary to think the publicity considering the relationship between persuasion and founding discourse or persuasion and identity, beyond the themes of traditional history of advertising. This paper aims to examine some of the different promotional materials used by the government Dilma. The research is based primarily on the analysis of French Discourse and aims to understand the language in their dynamics, making the symbolic sense, that is, without a doubt, a constitutive part of man's life as a way to signify. By analyzing the discursive and ideological formations of promotional materials Dilma government, focus - the following questions: how these advertisements produce effects of meaning? What are the possibilities for framing or disciplining of subjects in the discursive formation / ideological dominance, which occurs by the mechanism of anticipation, when the subject-author protrudes imaginatively in the place where the other awaits? 03 advertisements were selected television advertising that allow to analyze how the effects are felt in the speech. They are part of a sequence of advertisements referred to as 03 'in Brazil safe hands ". They are: Brazil in good hands - education; Brazil in good hands - the economy and Brazil in good hands - large projects. The advertisements were captured on the website Youtube. Corpus analysis was performed by the formation of segments discursive frame by frame advertising material collected, taking into account the discursive and ideological formations, production conditions, and interdiscursivity event, concepts that are affiliated with the AD. In the analyzes it was possible to see how, through the mechanism of anticipation, the individual producer's advertising discourse mobilizes senses surfacing elements related to power that are crystallized in the Memory of the discursive subject viewer. These different meanings lead to understand that advertising is not ahistorical or asocial and the clearances and dispersions can attest to his character living history. Advertising materials work with the redefinition of the subject of what has been said, introducing a new discursive process that, when applied to the new mean, inscribes the subject in the position that suits the ruling class. This time, it was possible to understand that advertising advertising constitutes an important tool for understanding the discourse that circulates in and through language.